2018
DOI: 10.1080/13557858.2018.1492707
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant intake in relation to serum C-reactive protein in mid-life and older African Americans

Abstract: Our study does not support the inverse relationship between antioxidants intake and CRP, but does support the evidence for obesity-induced inflammation and suggests the association can be applied to AA women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Among inflammatory biomarkers evaluated in a cohort of elderly individuals supplemented with a combination of Se and coenzyme Q 10 in the Swedish KiSel project [12], the markers CRP, P-selectin [45] and osteoprotegerin (OPG) [46] were reduced or normalized following a four-year period of supplementation. In another cohort encompassing elderly women, Se supplementation was observed to ameliorate obesity-induced inflammatory responses [47]. Insulin-like growth factor 1 (IGF-1), considered to be a central biomarker in nutrition and inflammation [48], did increase following selenium supplementation [49].…”
Section: Ageing and Inflammationmentioning
confidence: 99%
“…Among inflammatory biomarkers evaluated in a cohort of elderly individuals supplemented with a combination of Se and coenzyme Q 10 in the Swedish KiSel project [12], the markers CRP, P-selectin [45] and osteoprotegerin (OPG) [46] were reduced or normalized following a four-year period of supplementation. In another cohort encompassing elderly women, Se supplementation was observed to ameliorate obesity-induced inflammatory responses [47]. Insulin-like growth factor 1 (IGF-1), considered to be a central biomarker in nutrition and inflammation [48], did increase following selenium supplementation [49].…”
Section: Ageing and Inflammationmentioning
confidence: 99%
“…et al reported that in a cohort encompassing elderly women, selenium supplementation was observed to ameliorate obesity-induced inflammatory responses. There was an increase in insulin-like growth factor 1, a central biomarker in inflammation, 10 following selenium supplementation. 10 , 11 There are, however, limited studies that compare the selenium status, levels of inflammatory markers and oxidative stress between patients with ICM and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…There was an increase in insulin-like growth factor 1, a central biomarker in inflammation, 10 following selenium supplementation. 10 , 11 There are, however, limited studies that compare the selenium status, levels of inflammatory markers and oxidative stress between patients with ICM and healthy controls. The impact of selenium on inflammation in the population with ICM requires further study.…”
Section: Introductionmentioning
confidence: 99%